PROFIL HEMATOLOGIS DAN DETEKSI MOLEKULAR PEMBAWA SIFAT HEMOGLOBIN E DI YOGYAKARTA - , Magfirahtul Jannah, Dr.biol.hom Nastiti Wijayanti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hemoglobin E (HbE) is the most common structural hemoglobin variant disorders in South East Asia, including Indonesia. It is resulting from substitution of Gï A at codon 26 exon 1 HBB gene, leading to replacement of glutamic acid into lysine. HbE mutation leading to a decrease in the synthetic rate of Î²-globin chain. HbE disease and carrier are asymptomatic, but HbE carrier have an increase in the concentration of HbA2 by more than 13%. Restriction fragment length polymorphism (RFLP) with the MnlI restriction enzyme used to detect HbE mutations. This study aims to perform molecular detection using RFLP technique as a confirmatory test to the results of hematological analysis. Specimens of research is blood samples of thalassemia screening participants in 2013 were carried out by the Yayasan Thalassemia Indonesia/Persatuan Orangtua Penyandang Thalassemia Indonesia (YTI/POPTI) branch of Yogyakarta and the Faculty of Biology UGM. Research subjects consisted of 8 mens and 20 womens with an age range 1-37 years, who had the inclusion criteria and normal control. DNA was isolated from the blood of each individual and amplified using forward 5â-AGAAGTCTGCCGTTACTGCC-3â and reverse 5â-AGGCCATCACTAAAGGCACC-3â primers in the HBB gene sequences. The amplification product then analyzed by RFLP technique using the MnlI restriction enzyme. Interpretation of the data is done by comparing the differences in the size and number of DNA fragments digested between normal individuals and suspect carrier, then analyzed with the results of hematological analysis. The results showed that 10 individuals (35,71%) with abnormalities on the corpuscular indices and the peripheral blood picture of hematological analysis confirmed as HbE carrier using RFLP, while HbE disease is not found. RFLP with the MnlI restriction enzyme can be used as a confirmatory test to the results of hematological analysis of HbE carrier.